Kata Kerja Mengatakan dalam Tuturan Bahasa Banjar - Rissari Yayuk (Kelasa, 2019)
Verbs say are often used in everyday communication. These words are usually structurally predicate in sentences.However, the pragmatic semantics of these words can be used in a variety of functions and types of speech. This research is titled verbs say in Banjar language speech. The problem under consideration is the use of verbs to mean significant in affix in Banjar language and Banjar language speech strategy using verbs. The purpose of the study is to describe the use of verbs to say meaningful affixes meN- in the language of Banjar and Banjar language speech strategies that use the verb says. This study uses a structural, semantic, and pragmatic perspective. The method of this research is descriptive. Techniques used in data retrieval are recording and documentation techniques. Method of data analysis is by qualitative way. Data presentation techniques using ordinary words. The results of the study concluded that the use of verbs means that the meN- affix in Banjar speech includes the commanding verb, giving information, agreement, and expectation. The banjar language spoken language strategy using the verb says. Includes paying attention to the needs of the said partners, involving the said partner. Avoiding discrepancies, and growing an optimistic attitude. AbstrakKata kerja mengatakan digunakan dalam komunikasi sehari-hari. Kata ini memiliki fungsi predikat dalam kalimat. Kata ini dapat digunakan dalam ragam fungsi dan jenis tuturan. Masalah penelitian yaitu makna kata mengatakan imbuhan meN- dan strategi menggunakan kata kerja mengatakan dalam tuturan bahasa Banjar. Tujuan penelitian adalah mendeskripsikan penggunaan makna kata mengatakan imbuhan meN- dan strategi menggunakan kata kerja mengatakan dalam tuturan bahasa Banjar. Penelitian ini menggunakan teori struktural, semantik, dan pragmatik. Metode penelitian ini adalah deskriptif. Teknik yang digunakan dalam pengambilan data adalah teknik  rekam dan dokumentasi. Teknik penyajian data dengan menggunakan kata-kata biasa.  Hasil penelitian yaitu makna imbuhan meN- dalam kata kerja mengatakan  dalam tuturan bahasa Banjar  meliputi kata kerja memerintah, memberikan informasi, perjanjian, dan harapan. Strategi tuturan bahasa Banjar yang menggunakan kata kerja mengatakan meliputi  memperhatikan kebutuhan mitra tutur,  melibatkan mitra tutur, menghindari ketidakcocokan, dan menumbuhkan sikap optimis.